Kreativitas Guru dalam Mengelola Kelas untuk Mengatasi Kejenuhan Belajar Siswa di Madrasah Aliyah Negeri - Sofiyulloh (Tarbawi : Jurnal Studi Pendidikan Islami, 2022)
The creativity of the teacher in managing the classroom is very important because it will develop the success of the teacher in overcoming the boredom of student learning. The purpose of this study was to determine the creativity of teachers in the field of Islamic Education in managing classes to overcome learning saturation in Madrasah Aliyah Negeri and also to determine the symptoms of learning saturation faced by students in Madrasah Aliyah Negeri. This type of research is field research with a qualitative case study approach. The subjects of this study were 2 teachers in the field of Fiqh, 2 Al-Qur'an Hadith, 2 Akidah Akhlak, and 2 Islamic Cultural History teachers and also 6 students who participated in Islamic Education learning materials. The data collection techniques used were observation, interviews, and documentation, while the data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of this study indicate that the creativity of teachers in managing the classroom to overcome student boredom in Madrasah Aliyah Negeri has five points of findings, namely: 1) checking the situation and condition of students in order to understand and ensure that students are comfortable and happy in participating in learning, 2 ) teachers also make good use of learning media in learning, 3) teachers manage the learning environment well, 4) develop teaching strategies, 5) and provide motivational strategies. This research can contribute to teachers to review the circumstances and conditions experienced by students when teaching and learning activities are taking place in handling classes.